Openness to Change Non-Academic Staff of Higher Education Institution in South Kalimantan Region - Erlyani, Neka; Zwagery, Rika Vira; Fauzia, Rahmi; Raiyati, Siti; Regina, Ayu (Universitas Proklamasi 45, 2025)
The competition in the global education market at the national level requires both public and private universities in the South Kalimantan region, as they must continue to strive to adapt to the demands of change and government policies if they want to survive. Enhancing services is essential for efficient university governance, particularly in the administrative domain. Traditionally performing routine work, non-academic staff must demonstrate an openness to change to fulfill changing service expectations. This study examines the variables that affect non-academic staff members' openness to change, emphasizing the functions of transformational leadership, transparent communication, and organizational trust. The research employs a quantitative design, with a cross-sectional survey design. The 251 participants were selected through purposive sampling. The instruments used include adapted scales such as the Openness to Change Scale, the Multifactor Leadership Questionnaire Form 5X-Short, the Transparent Communication Scale, and the Organizational Trust Inventory-Short Form. The multiple linear regression was utilized to analyze the data. The results show that transformational leadership, transparent communication, and organizational trust collectively affected openness to change, but only organizational trust individually affected openness to change. Therefore, these factors must be carefully considered and maintained to enhance non-academic staff's openness to change within universities.